A review of spatial patterns across species ranges to aid the targeting of conservation interventions. (November 2020) - Burgess, Malcolm D.; Eaton, Mark A.; Gregory, Richard D.
Abstract: Conservation resources are limited and need to be used where they can be most effective. Deciding where within a species range to implement conservation interventions requires knowledge of where threats operate and consideration of multiple spatial issues concerning patterns in abundance across species' ranges, and geographical and environmental gradients in these and other traits across species' ranges. Although these biogeographical patterns have been of great interest to ecologists for many years, the implications of these patterns for conservation are often unclear. Here we review these patterns in the context of targeting spatial conservation. We find that an inconsistent use of terminology, a lack of consistent rules and the use of imperfect datasets, hampers us drawing firm conclusions on the nature of these patterns. Evidence that abundance and ecological traits change systematically towards range edges is inconclusive. Abundance variation is influenced by many factors independent of position within a species range, including habitat type, habitat quality, environment, interspecific competition, dispersal ecology and metapopulation dynamics. This results in complex textured abundance patterns compared to a simple theoretical core-edge gradient. We conclude that any conservation practitioner looking to target the location of interventions will need to examine these patterns and processes for the species of interest. Current knowledge does not adequately inform spatial conservation prioritization for single-species conservation programmes and incorporating the complexities of spatial processes is challenging. The development of tools to inform spatial targeting of resources for single- or multiple-species conservation is required urgently to enable better use of conservation resources. Highlights: Conservation resources are limited and need to be used effectively. Single species conservation should consider range-wide ecological patterns. Inconsistent terminology, a lack of rules and imperfect datasets hamper synthesis. Current knowledge does not inform spatial conservation prioritization adequately.